Construction of a highly saturated genetic map and identification of quantitative trait loci for leaf traits in jujube - Yan, Fenfen; Luo, Yujia; Bao, Jingkai; Pan, Yiling; Wang, Jiurui; Wu, Cuiyun; Liu, Mengjun (Frontiers in Plant Science, 2022)
Jujube (Ziziphus jujuba Mill.) is the most important species of both genus Ziziphus and family Rhamnaceae in terms of its economic, ecological and social benefits. To dissect the loci associated with important horticultural traits and to analyze the genetic and genomic information in jujube, a whole-genome resequencing (WGR) based highly saturated genetic map was constructed using an F1 hybrid population of 140 progeny individuals derived from a cross of ‘JMS2’×‘Jiaocheng 5’. The average sequencing depth of the parents was 14.09× and that of the progeny was 2.62×, and the average comparison efficiency between the sample and the reference genome was 97.09%. Three sets of genetic maps were constructed for female parent, male parent and integrated. In the integrated map, a total of 8,684 markers including 8,156 SNP and 526 InDel markers were well-distributed on all the 12 linkage groups (LGs), spanning 1,713.22 cM with an average marker interval of 0.2 cM. This is the most saturated genetic map of jujube so far, nearly double that of the best ones reported before in terms of both marker number and density. Based on this genetic map and the phenotype data from 2019 to 2021, a total of 31 leaf trait QTLs, including 17 major QTLs, were identified in the linkage groups (LG1, 15; LG3, 1; LG5, 8; LG7, 4; LG8, 1 and LG 11, 2). Of them, 4, 8, 14 and 5 QTLs contributed to leaf length, leaf width, leaf shape index and leaf area, respectively. A total of six QTLs clusters were detected on LG1(8.05-9.52cM;13.12-13.99cM;123.84-126.09cM;), LG5(50.58-50.86cM;80.10-81.76cM) and LG11(35.98-48.62cM). A total of 8 candidate genes were identified within the QTLs clusters regions.Annotation information showed that 4 genes (LOC107418196,LOC107418241,LOC107417968 and LOC112492570) in these QTLs are related to cell division and cell wall integrity. This research will provide a valuable tool for further QTLs analyzing, candidate genes identifying, map-based gene cloning, comparative mapping, and marker-assisted selection (MAS) in jujube.